SAT0151 Cardiorespiratory fitness in patients with rheumatoid arthritis. (12th June 2018) - Liff, M. H.; Hoff, M.; Fremo, T.; Wisløff, U.; Thomas, R.; Videm, V.
Abstract : Background: Mortality rates are higher in RA patients compared to the general population, mostly due to cardiovascular disease (CVD). Cardiorespiratory fitness (CRF) is inversely associated with CVD, but little is known about CRF levels in RA patients. Objectives: To study the association between CRF in RA patients (measured as VO2 peak), and CVD risk factors and RA-specific clinical variables. Methods: 93 patients were recruited from a hospital rheumatology outpatient clinic. VO2 peak was measured by ergospirometry during a treadmill test. Tender and swollen joint count, height, weight, waist circumference, resting heart rate, blood pressure and hsCRP were measured. RA characteristics and information on comorbidity were recorded from an interview and from medical records. Based on a previously published index weighting frequency, intensity and duration of self-reported physical activity (PA) (1), patients were categorized into four different PA categories (table 1). VO2 peak was analyzed using multivariate linear regression, adjusting for age and gender. All participants signed an informed consent and the regional ethics committee approved the study. Results: Conclusions: We observed a strong association between common CVD risk factors (inactivity, high BMI, high resting heart rate) and lower CRF in RA patients, similar to published findings from the general population. Patients in the "Active" and "Very active" PA categories showed significantly higher VO2 peak, whereas RA-specific variables such as seropositivity, disease activity, disease duration and medications had no impact on VO2 peak. We cannot exclude a selection bias because more fit patients could be more likely to participate in the study. Reference: [1]Nes BM, Janszky I, Vatten LJ, Nilsen TI, Aspenes ST, Wisloff U. Estimating VO2 peak from a nonexercise prediction model: the HUNT Study, Norway. Med Sci Sports Exerc2011;43(11):2024–30. Acknowledgements: The VO2 peak testing was performed at the core facility NeXt Move, NTNU – Norwegian University of Science and Technology. Disclosure of Interest: None declared